Synthesis of isomeric corniculatolides - Raut, Gajanan N.; Chakraborty, Kasturi; Verma, Priyanka; Gokhale, Rajesh S.; Reddy, D. Srinivasa (Tetrahedron Letters, 2012)
Synthesis of three natural macrolides 11-O-methylcorniculatolide A, 11-O-methylisocorniculatolide A and isocorniculatolide A is reported using a simple, straight forward and high-yielding route. The present synthesis confirms the assigned molecular structures and provides an access to sufficient quantities of the natural products for the biological evaluation. In addition, we have determined the anti-TB potential of the three natural compounds using Alamar-Blue assay (H(37)Rv) and found no significant inhibitory activity at 100 mu g/ml. Excellent yields, short sequence and useful SAR information are the highlights of the present work. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Diaryl ether; Isocorniculatolide; Macrocyclization; Mitsunobu reaction; Total synthesis

Synthesis of revised structure of klaivanolide (acetylmelodorinol) - Raut, Gajanan N.; Wagh, Sachin B.; Reddy, D. Srinivasa (Arkivoc, 2016)
Klaivanolide (acetylmelodorinol) is an anti-leishmanial/anti-trypanosomal agent isolated from Uvaria klaineana and the structure was originally assigned as a 7-membered lactone with extended conjugation and S-configuration at the lactone junction. Very recently, the structure of klaivanolide was revised as previously known compound acetylmelodorinol. Now, we have synthesized the revised structure in racemic form using a short route.
Keywords: acetylmelodorinol; Klaivanolide; leishmaniasis; Natural product